RESIDENTIAL ROOM PLACEMENT STRATEGY AS AN EFFORT TO PREVENT PRISONER RESISTANCE IN CLASS II B WARUNGKIARA CORRECTIONAL INSTITUTION - Irmansyah, Ari; Kurniawan, Andi (Universitas Nusa Cendana, 2025)
Overcapacity in prisoner in Indonesia is a potential serious problem such as prisoner resistance. This study intend to analyse the strategy of residential room placement as a means to prevent prisoner resistance in Warungkiara Class II B Correctional Facility. This research uses a descriptive qualitative method involving in-depth interviews with prison officials and prisoners to gain a comprehensive understanding of the dynamics that occur within the institution. The results show that Warungkiara’s Prisoner has implemented a placement strategy based on various criteria, including gender, age, criminal offence, and coaching needs. The research identifies several significant obstacles, such as high levels of overcrowding and staff shortages that impact the effectiveness of the placement strategy, creating challenges in maintaining security, order and increasing the potential for resistance among prisoners. The study concludes that the proper prisoner rooms can serve as a preventive measure in reducing the risk of prisoner resistance. Keywords: Prisoner Room Placement; Prisoner Resistance; Prison; Overcapacity